The genetic spectrum of familial hypercholesterolemia in the central south region of China. (March 2017) - Xiang, Rong; Fan, Liang-Liang; Lin, Min-Jie; Li, Jing-Jing; Shi, Xiang-Yu; Jin, Jie-Yuan; Liu, Yu-Xing; Chen, Ya-Qin; Xia, Kun; Zhao, Shui-Ping
Abstract: Background and aims: Familial hypercholesterolemia (FH) is the most common and severe autosomal dominant lipid metabolism dysfunction, which causes xanthoma, atherosclerosis and coronary heart disease. Earlier studies showed that mutations in LDLR, APOB and PCSK9 cause FH. Although more than 75% of the population in Europe has been scrutinized for FH-causing mutations, the genetic diagnosis proportion among Chinese people remains very low (less than 0.5%). The aim of this study was to perform a survey and mutation detection among the Chinese population. Methods: 219 FH patients from the central south region of China were enrolled. After extracting DNA from circulating lymphocytes, we used direct DNA sequencing to screen each exon of LDLR, APOB and PCSK9 . All detected variants were predicted by Mutationtaster, Polyphen-2 and SIFT to assess their effects. Results: In total, 43 mutations were identified from 158 FH patients. Among them, 11 novel mutations were found, including seven LDLR mutations, two APOB mutations and two PCSK9 mutations. Moreover, five common mutations in LDLR were detected. We geographically marked their distributions on the map of China. Conclusions: The spectrum of FH-causing mutations in the Chinese population is refined and expanded. Along with future studies, our study provides the necessary data as the foundation for the characterization of the allele frequency distribution in the Chinese population. The identification of more LDLR, APOB and PCSK9 novel mutations may expand the spectrum of FH-causing mutations and contribute to the genetic diagnosis and counseling of FH patients. Highlights: We have detected 219 Chinese FH patients, and this survey may be the largest FH mutation detection in the Chinese population. 11 novel mutations including seven LDLR mutations, two APOB mutations and two PCSK9 mutations were identified. Five common mutations of LDLR have been identified and marked on the map of China.